Kesiapan Menikah pada Generasi Z: Marital Attitudes dan Kematangan Emosi - Herawati, Icha; Yendra, Dinda; Amita, Nindy (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
Marriage readiness is an essential factor that should be carefully considered before deciding to marry. Individuals who choose to enter marriage are expected to possess emotional maturity and stability, as these aspects significantly contribute to their ability to manage the demands and responsibilities of marital life. This study aims to examine the influence of emotional maturity and marital attitudes on marriage readiness among Generation Z. A quantitative approach using multiple linear regression analysis was applied to data collected from 400 unmarried Generation Z individuals in Pekanbaru City, Indonesia. The results revealed that both emotional maturity and marital attitudes had a positive and significant effect on marriage readiness (R = 0.643, R² = 0.414, p < 0.001), indicating that 41.4% of the variance in marriage readiness was explained by the two predictors, while the remaining variance was attributed to other factors. More specifically, emotional maturity (β = 0.449, p < 0.001) showed a stronger influence than marital attitudes (β = 0.372, p < 0.001), suggesting that emotional regulation, self-control, and psychological stability play a dominant role in shaping individuals’ readiness for marriage. These findings highlight the importance of developing premarital counseling and emotional management programs to help young adults enhance their readiness for a stable and harmonious marital life.